Tratamiento ordinal de las escalas cualitativas utilizadas por el Centro de Investigaciones Sociológicas; Ordinal treatment of qualitative scales used by the Center for Sociological Research - Raquel González del Pozo; José Luis García-Lapresta (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– Qualitative scales formed by linguistic terms are used by different disciplines to determine preferences and different aspects of individuals' lives. Although it is usual to assign numbers to the response categories of scales, it is not suitable when individuals perceive different proximities between the consecutive categories of the scale, that is, when scales are not uniform. In this paper, an ordinal procedure is proposed to order a set of alternatives from the assessments given by a group of individuals through a qualitative scale not necessarily uniform. This procedure is based on ordinal proximities between the response categories of scales. The proposed procedure is illustrated with an example taken from the Barometer of the Center for Sociological Research of May 2011.
Keywords: C20; C83; 330; surveys; questionnaires; qualitative scales; imprecision; CIS